Rationality of fare increment for improvement of transfer facilities at metro stations: An experience in Kolkata. (August 2017) - Sadhukhan, Shubhajit; Banerjee, Uttam K.; Maitra, Bhargab
Abstract: There are several lacunas associated with the public transport quality and allied facilities in emerging countries such as India. The improvement of these facilities is a major challenge as most of the Governments are not only finding it difficult to provide an additional subsidy for the improvement but are also hesitant to increase the fare because of socio-political reasons. In this context, the present paper demonstrates an approach for investigating the rationality of fare increment with reference to a case study of transfer facilities at metro stations in Kolkata city, India. Rationality of the fare increment is judged by comparing the fare increment with (i) benefits likely to be transferred to commuters due to improvement, (ii) present fare, and (iii) average daily income of metro commuters. The work also highlights the need for quantifying the benefits likely to be transferred to commuters from the proposed improvements for relating the fare increment to derived benefits. It is shown that if the fare increment is found rational then facilities should be developed by recovering the associated cost from commuters without putting the additional financial burden on the Government. The Government subsidy should be introduced only when it is required to bring down the fare increment to a level which is considered rational. The findings will hopefully encourage policy makers to apply the approach to other contexts for improvement of transport facility or quality of service with a rational increment of fare and use of Government subsidy, as and when required. Highlights: Willingness-to-pay values for improvement of transfer facilities are estimated. User's benefits for improvement of various transfer facilities are calculated. Life-cycle costs of various improvements of transfer facilities are estimated. Improvement costs are compared with user's benefit, present fare and income. Rationality of fare increment for improvement of transfer facilities is judged.